Hydrogen as a future topic in German VET? — Research design and initial findings from the research project H2PRO - Schneider, Maximilian [Verfasser] (My University, 2023)
"Context: Hydrogen is a crucial element in the transition towards a green economy. In various sectors, hydrogen opens up decarbonization paths where direct or battery electric systems cannot meet high energy demands or where no other alternatives to fossil raw and auxiliary materials are applicable. Qualified workers are a crucial factor for the successful establishment of the hydrogen economy. The research project H2PRO at the German Federal Institute for Vocational Education and Training (BIBB) addresses the questions of how skills requirements in training occupations change due to hydrogen, and what measures are necessary in German vocational education and training policy and practice to support hydrogen-related skills development. Methods: The project uses a qualitative research design consisting of sector analyses, expert interviews, and case studies, and examines the entire hydrogen value chain from production to application areas such as steel, chemicals, mobility, and heat supply. Findings: The contribution focuses on the mobility and transport sector, specifically on skilled workers in automotive workshops. At this point, initial results suggest that there is no need for a specific hydrogen training occupation. Instead, specific training offers are required in vocational education and training to address qualification gaps in specific occupations, ensuring that skilled workers are prepared to work with hydrogen technologies." (Authors' abstract, BIBB-Doku)
Keywords: G 1.2.4.2.2 Verkehr- und Nachrichtenübermittlung; G 2.3.4 Qualifikationswandel; 370; 330; Wasserstoffwirtschaft; Verkehrswesen; Qualifikationsbedarf; Qualifikationswandel; Green skills / grüne Kompetenzen